Generator & electrical system (Gas turbine power generation)
The objective of this module is to draw attention to important operating parameter of the power generator. A review of fundamentals is included as an aid to understanding the signficance of generator control. Topics include generator construction, hydrogen cooling, air cooling, excitation systems, control of MVARS, synchronizing, parallel operation and generator protection.